Widely tunable fiber optical parametric oscillators with idler removal filter - Kwok, Shien Yeo; Bakar, Muhammad Hafiz Abu; Adikan, Faisal Rafiq Mahamd; Mahdi, Mohd Adzir (Institute of Electrical and Electronics Engineers, 2017)
The properties of the singly resonant and double-pass pump fiber optical parametric oscillators (FOPO) are experimentally investigated. An idler removal filter is utilized to eliminate the idler component in a Fabry-Pérot cavity to minimize the effect of modulation instability. For singly resonant FOPO, the pump is also filtered out and leaves the signal to oscillate in the cavity. For double-pass pump FOPO, the idler removal filter is designed to allow propagation of signal and pump in the cavity. The results show that double-pass pump FOPO brings several important enhancements over the conventional singly resonant FOPO. Among them are the low threshold of 0.247 W with improvement by 51% at 0.45 W pump power. It is also found that the conversion efficiency of the two configurations has no significant difference.